Narrative Complexity in the Works of Toni Morrison (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the profound impact of Toni Morrison's literary works, focusing on her unique narrative style and thematic explorations of African American life, memory, and historical trauma. Through an analysis of her seminal novels Beloved, Song of Solomon, and Jazz the study highlights Morrison's innovative use of non-linear storytelling, intertextuality, and symbolic language. Morrison's works serve as cultural artifacts that not only portray the African American experience but also challenge dominant historical narratives. Her concept of 'rememory,' portrayal of collective memory, and literary jazz composition contribute to her distinctive storytelling.